Pengaruh Pengendalian Intern dan Komitmen Organisasi terhadap Kinerja Karyawan(Studi Kasus pada PT. Pegadaian (Persero) Cabang Sragen) - Aryati, Airin Novi; , Drs. Atwal Arifin, M.Si (2016)
This study aims to identify and analyze the influence of internal control and organizational commitment to performance karyawanpada PT. Pawnshop (Persero) Branch Sragen.Penelitian this is quantitative. The data used in this study are primary data. A sampling technique that using saturation sampling. The data collection of research conducted by distributing questionnaires to the number of 36 respondents. Methods of testing the validity of the instrument under test using Pearson product moment and reliability testing using alpha cronboach. Testing Classical Assumptions include Normality Test, Multicollinearity and Heteroskidastity. The data analysis technique used to test hypotheses include multiple linear regression, t-test, F, R2 test. Based on the analysis, internal control and commitment menunjukkanbahwa organisasiberpengaruhterhadap employee performance.